A maturity model for supply chain risk management - Guerra, João Henrique Lopes; Souza, Fernando Bernardi de [UNESP]; Pires, Silvio Roberto Ignácio; Sá, Anderson Luiz Ribeiro de (Emerald, 2024)
Purpose: Supply chains are among the most important, complex and risky systems in the modern world. Thus, managing risk is no longer an option, but a fundamental process in organizations. Given the lack of pathways that guide companies toward supply chain risk management (SCRM), the purpose of this study is to provide a conceptual reference, in the form of a maturity model, to support them in the evolution and improvement of this process. Design/methodology/approach: The proposal covered a broad literature review, a survey and a multiple case study. The research was conducted in the aerospace industry and included companies from the supply chain of a leading aircraft manufacturer. Findings: The model elaborated with the research results has eight attributes and four levels, addressing critical issues for SCRM to achieve its scope and purposes. The attributes include the structuring and scope of the SCRM process, the importance it receives within the organization, the resources used and the qualification of employees, the role of leadership and the inter-organizational collaboration. Practical implications: Managing risk along supply chains is particularly challenging, demands resources and knowledge and requires a continuous effort. The proposed model offers a reference for improvement, helping to identify areas that need to be strengthened and practices to be implemented. Thus, it can guide the focus and efforts in a more efficient and systematic way, in addition to support evaluations and comparisons. Originality/value: Although maturity models are abundant in different fields and several are available for risk management, models specifically developed for SCRM are scarce. This study broadens the understanding of SCRM with novel insights about how to improve this process in an evolutionary way. While many researchers focused their efforts on the SCRM process steps, this study identified critical issues that transcend these steps. The research was carried out in a sector with a long tradition in risk management and included companies belonging to a same supply chain, that is, using an approach still little explored in studies on SCRM or risk management maturity models.
Keywords: Aerospace industry; Supply chain management; Supply chain risk management